2022
DOI: 10.1111/oik.09202
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on fish swimming and schooling is context dependent

Abstract: Temperature is highly influential on the physiology and behaviour of ectotherms. In fish, temperature affects social interactions such as schooling behaviour, a common defence against predation. However, the effect of temperature on the ability of schooling fish to collectively respond to a predator is unknown. Here we used a loom stimulus to simulate an approaching predator that elicited a fleeing response in schooling fish over a range of water temperatures (9-29°C) and group sizes (1-16 fish). While speed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Previous work has also found that fish form tighter shoals at higher temperatures (Krause & Godin, 1995;Kuruvilla et al, 2022;Pitcher & Parrish, 1993;Pritchard et al, 2001;Weetman et al, 1998Weetman et al, , 1999.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Previous work has also found that fish form tighter shoals at higher temperatures (Krause & Godin, 1995;Kuruvilla et al, 2022;Pitcher & Parrish, 1993;Pritchard et al, 2001;Weetman et al, 1998Weetman et al, , 1999.…”
Section: Discussionmentioning
confidence: 83%
“…We observed an increase in shoaling at the higher temperature as measured by the local‐scale NND and one of the global scale measures (the index of dispersion), although no effect on the other global measure of cohesion, the mean inter‐individual distance, was found. Previous work has also found that fish form tighter shoals at higher temperatures (Krause & Godin, 1995 ; Kuruvilla et al, 2022 ; Pitcher & Parrish, 1993 ; Pritchard et al, 2001 ; Weetman et al, 1998 , 1999 ). This may be a response to increased risk perception, as higher temperatures also increase predators' metabolic requirements and speed (Domenici et al, 2019 ; Ohlberger et al, 2012 ), although this is not supported by our experiment as here the measure of risk perception used (refuge use) was reduced at higher temperatures, suggesting that the fish were bolder.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In fish, beside mechanistic changes in motility, temperature fluctuations can have positive or negative effects on antipredator behaviour depending on a variety of factors, such as predator presence (Weetman et al, 1999), life stage (Colchen et al, 2016), mixed-species shoals (Mitchell et al, 2022;Paijmans et al, 2020) or activity levels of potential shoal mates (Pritchard et al, 2001). This suggests that the effects of increased temperature on behavioural traits are context dependant (Kuruvilla et al, 2022).…”
Section: Introductionmentioning
confidence: 99%